Retração palpebral em infra-dextro-versão: relato de caso - Schellini, Silvana Artioli [UNESP] (1999)
We present a 31/2 year-old ortophoric patient, with normal function of the elevator muscle and with upper right eyelid retraction on right down gaze when lying down. The eyelid retraction is not released by any other maneuver. The possible causes for the eyelid retraction are discussed.